Efficacy and safety of rivaroxaban versus placebo after lower extremity bypass surgery: A post hoc analysis of a "CASPAR like" outcome from VOYAGER PAD. Issue 12 (17th October 2022) - Bonaca, Marc P.; Szarek, Michael; Debus, E. Sebastian; Nehler, Mark R.; Patel, Manesh R.; Anand, Sonia S.; Muehlhofer, Eva; Berkowitz, Scott D.; Haskell, Lloyd P.; Bauersachs, Rupert M.
Abstract: Background: The Clopidogrel and Acetylsalicylic Acid in Bypass Surgery for Peripheral Arterial Disease (CASPAR) trial is the only large, double‐blind, placebo‐controlled trial of dual antiplatelet therapy (DAPT) versus aspirin in patients with peripheral artery disease (PAD) after lower extremity revascularization (LER). The trial was neutral for index‐graft occlusion/revascularization, amputation or death (hazard ratio [HR] 0.98, 95% confidence interval [CI] 0.78–1.23, p = .87) with an excess of global utilization of streptokinase and tissue plasminogen activator for occluded coronary arteries moderate or severe bleeding (HR 2.84, 95% CI 1.32–6.08, p = .007). Hypothesis and Methods: VOYAGER‐PAD demonstrated that rivaroxaban significantly reduces acute limb ischemia (ALI), major amputation, myocardial infarction (MI), stroke and CV death but increased bleeding. The relative efficacy and safety of rivaroxaban in a CASPAR like population and for similar outcomes is unknown. The current analysis is a post‐hoc exploratory analysis of a "CASPAR like" composite of ALI, unplanned index limb revascularization (UILR), amputation or CV death in surgical patients. Results: In the 2185 who underwent surgical LER, rivaroxaban reduced the CASPAR endpoint at 1 (HR 0.76, 95% CI 0.62−0.95, p = .0133) and 3 years (HR 0.84, 95% CI 0.71−1.00, p = .0461, Figure). There were similar reductions in composites of ALI, amputation or CV death (HR 0.79, p = .0228) and ALI, UILR, amputation, MI, IS or CV death (HR 0.85, p = .0410). Conclusions: The combination of rivaroxaban and aspirin significantly reduces ischemic outcomes in patients with PAD after LER. Although no formal head‐to‐head comparison exists, in a similar population and for similar outcomes, this regimen demonstrated benefit where trials of DAPT were neutral. These data suggest that factor Xa inhibition may provide specific benefits in this population and that DAPT should not be considered a proven substitution.